Pengaruh Modal Kerja, Aktivitas, Likuiditas dan Solvabilitas Terhadap Profitabilitas Pada Perusahaan Sub Sektor Perdagangan Besar yang Terdaftar di Bursa Efek Indonesia - Miea Sari; Dedi Hariyanto; Heni Safitri (Jurnal Produktivitas: Jurnal Fakultas Ekonomi Universitas Muhammadiyah Pontianak, 2018)
The purpose of this study are: Use Inventory Turn Over and Working Capital Turn Over, Liquidity uses the ratio of Current Ratio and Quick Ratio, and Solvability uses the ratio of Debt to Asset Ratio and Debt to Equity Ratio to Profitability using the Return ratio of Investments in Wholesale Trading Sub-Sector Companies .Based on F value it can be seen that together independent variables have a significant effect on the dependent variable. This can be evidenced from the calculated F value of 0.7440 and has a significant value of 0.000 which is smaller than 0.05, meaning working capital, Inventory Turn Over, Working Capital Turn Over, Current Ratio, Quick Ratio, Debt to Asset Ratio, Debt to Equity Ratio together has a significant influence on Return On Investment. The results of the t test (partial) Debt to Asset Ratio (X6) have a significant effect on Return on Investment (Y) while working capital (X1), Inventory Turn Over (X2), Working Capital Turn Over (X3), Current Ratio (X4), Quick Ratio (X5), Debt to Equity Ratio (X7) does not have a significant influence on Return on Investment (Y).